MASS SPECTROMETRIC IDENTIFICATION OF BLOODSTREAM INFECTION AGENTS: EXPERIENCE IN PEDIATRIC PRACTICE - Kodirov Khusanboy Solievich (Scholar Express Journals, 2025)
Rapid diagnostics of bloodstream infections is a pressing issue in modern pediatrics. The paper presents data from a comparative analysis of two methods for identifying microorganisms in the blood of children with suspected bloodstream infections: routine microbiological testing and MAldITOF mass spectrometry. The results obtained using the mass spectrometric (MAldI-TOF) method for identifying microorganisms in blood cultures from children with bloodstream infections containing one pathogen are highly consistent with the results of classical microbiological testing (Cohen's kappa 0.97, p < 0.001). MAldI-TOF mass spectrometric identification of bloodstream infection pathogens can be recommended as an additional diagnostic method aimed at reducing analysis time.
Keywords: bloodstream infections; bacteria; microscopic fungi